Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 775: 1


$m=1$ and $m=-6$

Work Step by Step

$m^{2}+5m-6=0$ Use the quadratic formula to solve this equation. The formula is $m=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$ In this equation, $a=1$, $b=5$ and $c=-6$ Substitute: $m=\dfrac{-5\pm\sqrt{5^{2}-4(1)(-6)}}{2(1)}=\dfrac{-5\pm\sqrt{25+24}}{2}=...$ $...=\dfrac{-5\pm\sqrt{49}}{2}=\dfrac{-5\pm7}{2}$ Our two solutions are: $m=\dfrac{-5+7}{2}=1$ $m=\dfrac{-5-7}{2}=-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.